Efficiency Analysis of Additions of Ice Flake in Cargo Hold Cooling System of Fishing Vessel - Amiadji Amiadji; Edi Jadmiko; Yosef Novian Prasetyo (International Journal of Marine Engineering Innovation and Research, 2017)
As a maritime nation, the majority of people's livelihood in Indonesia coast is as a fishermen. The process of preserving fish after being caught will determine how good the product quality. One of process on preserving fish that can be done is to perform the cooling process using a cooling machine on board. Refrigeration system certainly requires high electrical power consumption. That high power usage can be reduced as much as possible, one of which is to add chopped ice (ice flake) on a fishing boat cargo space. So that the load for cooling can be reduced.The purpose of this thesis is to find out how the influence of the addition of ice flake on cooling load in the cargo hold of fishing vessels, and to know how much power is used when the cooling machine is combined with the addition of ice flake. In this analysis cooling load calculation refers to the standard ISO 7547.from the results of analysis found that the addition of ice flake on cargo space can reduce cooling load and can reduce electricity consumption day in the main vessel for the addition comparison flake ice and fish weight of 1: 1.